2011
DOI: 10.1063/1.3592250
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation induced ferromagnetism at room temperature in TiO2 thin films: X-ray magnetic circular dichroism characterizations

Abstract: Room temperature ferromagnetic behavior in cluster free, Co doped Y2O3 dilute magnetic oxide films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 17 publications
3
25
0
Order By: Relevance
“…However, in their study, the O K-edge was not analyzed, despite that the spectra show similar features as those discussed in this paper. Thakur et al [20] identified two features in the O K-edge located around ∼1.2 eV at higher energies from the t 2g and e g bands after heavy ion irradiation on TiO 2 . They assigned the presence of these features to local distortions induced by irradiation [21], but no theoretical support or references were provided.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in their study, the O K-edge was not analyzed, despite that the spectra show similar features as those discussed in this paper. Thakur et al [20] identified two features in the O K-edge located around ∼1.2 eV at higher energies from the t 2g and e g bands after heavy ion irradiation on TiO 2 . They assigned the presence of these features to local distortions induced by irradiation [21], but no theoretical support or references were provided.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we correlate the theoretical CB of rutile TiO 2 , calculated by DFT, with experimental O K-edge measured by XAS at a synchrotron line from single phase rutile TiO 2 nanoparticles. Recent papers [19][20][21][22] aim to correlate O K-edge with structural defects in nanosized TiO 2 in order to explain their electronic, magnetic, and photocatalytic properties, but a correlation with theoretical approach, as included in this paper, was still needed. These nanoparticles have been previously analyzed by different techniques, such as transmission electron microscopy (TEM), cathodoluminescence (CL), and XPS [23], which will help to optimize the parameters used in our calculations.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that energetic ion irradiation induced defects in such oxide semiconductors can gives rise to interesting properties such as phase transitions, [22][23][24] Fermi level modification, 25 d 0 magnetization, 26 of understanding of the phonon evolution in oxide semiconductors. 27 Therefore, in the present manuscript, the density of structural defects and lattice strain induced by energetic ions and origin or validity of various models as discussed above have been selectively tested by minimizing other possible mechanisms as reported in the literature.…”
mentioning
confidence: 99%
“…It challenges the mJ paradigm for magnetism, where m refers the local moment and J stands for the interaction between the local moments. Experimentally, defect-induced ferromagnetism was observed in many materials, including graphite [2][3][4][5] and various oxides [6][7][8][9][10][11][12]. SiC single crystals are emerging as another candidate for this investigation and have been shown to be ferromagnetic after particle irradiation [13,14] or after aluminum doping [15].…”
Section: Introductionmentioning
confidence: 99%